Enhancing workplace physical activity for staff: a path to improved well-being / Dr. Farah Adilla Ab Rahman and Kamarul Aini Hassan Basri - Ab Rahman, Farah Adilla; Hassan Basri, Kamarul Aini (Universiti Teknologi MARA, Negeri Sembilan, 2024)
“Workplace physical activity significantly boosts employees' overall well-being.” Workplace physical activity is crucial for enhancing employee health and well-being, particularly in demanding sectors like academia and healthcare. Research indicates that physical activity at work is intricately linked to improved well-being [1]. In the healthcare sector, workers often face fatigue, burnout, and other health issues due to the demanding nature of their jobs, which negatively impacts their productivity, and the quality of care provided [2]. Similarly, academic staff may suffer from diminished well-being due to insufficient physical activity, which in turn impacts their performance. While individual-level interventions like regular exercise and healthy eating are beneficial, more comprehensive workplace solutions are needed to ensure long-term health and productivity.